Evaluation of IL-2, IL-10, IL-17 and IP-10 as potent discriminative markers for active tuberculosis among pulmonary tuberculosis suspects. (July 2016) - You, Eunkyoung; Kim, Myeong Hee; Lee, Woo-In; Kang, So Young
Summary: Introduction: Although interferon gamma release assays (IGRAs) are useful for specifically detecting Mycobacterium tuberculosis, they are limited by their inability to differentiate between active tuberculosis (active TB), latent tuberculosis infection (LTBI), and patients with prior TB infection. The purpose of this study was to rapidly and accurately identify active TB patients among patients with suspected respiratory TB by combining interferon-gamma (IFN-γ) with additional cytokines. Materials and methods: The present study was conducted on patients who required TB screening to discern active TB due to respiratory complaints. Among all patients screened, 80 who tested positive in the QunatiFERON TB GOLD in-tube assay (QFT-GIT) were retrospectively selected and divided into the active TB group (n = 40) and the non-active TB group (n = 40). Supernatants from the Nil tube and TB antigen (Ag)-stimulated tube from the QFT-GIT test were used. Interleukin (IL)-2, IL-10, IL-17, and IP-10 were measured by enzyme-linked immunosorbent assay (ELISA). Results: In comparing the differences significant differences in TB Ag tube response of IL-17 and IP-10, and 'TB Ag – Nil' response of IL-10 and IP-10 were evident between the active TB and non-active TB groups. From the calculation of diagnostic performance for differentiating active TB patients from QFT-positive patients, among the measured values, the value of IL-17 TB Ag tube with the cut-off value set to ≤0.82 (AUC 0.742) showed sensitivity, specificity, positive predictive value, and negative predictive value of 69.2%, 97.5%, 96.4%, and 76.5%, respectively. Discussion: Among TB suspects, IL-17 TB Ag response had the highest ability to distinguish active TB followed by IP-10 TBAg-Nil response and the IL-17/IFN-γ-TB Ag response combination improved the detection response. Differentiating active TB is best done using IL-17 as a biomarker, with IP-10 and IL-10 being potential useful.